P302 Trends in hospital admissions in patients with ANCA-associated vasculitis before and during the COVID-19 pandemic. (23rd April 2022) - Odingo, Myron; Rutter, Megan; Lanyon, Peter; Grainge, Matthew; Groves, David; Bythell, Mary; Aston, Jeanette; Stevens, Sarah; Pearce, Fiona
Abstract: Background/Aims: People with ANCA-associated vasculitis (AAV) have high rates of hospital admissions. They may have emergency admissions at the time of diagnosis, or day case admissions to receive immunosuppressive treatment. We describe the trends in emergency and day case admissions over the past 9 years, and the effect of the COVID-19 pandemic. Methods: We extracted hospital episode statistics available publicly from NHS Digital for 2012/13 to 2019/20 and added provisional data from the National Congenital Anomaly and Rare Disease Registration Service for 2020/21 under their legal permissions (CAG 10-02(d)/2015) because the publicly available data had not yet been released. We extracted all emergency and day-case admission rates with ICD codes for each AAV subtype (M301, M313 and M317, in the primary position denoting main admission diagnosis). We used England population estimates from the Office for National Statistics as the denominator for rates. We calculated Poisson confidence intervals to quantify the difference in rates between 2019/20 and 2020/21 financial years. Results: Rates of day case admissions per 1, 000, 000 for AAV increased from 49.1 (47.2 - 50.9) in 2012/13 to 63.3 (61.2 - 65.4) in 2019/20, then decreased by 26.4% to 48.6 (46.7 - 50.4) in 2020/21 (Table). The trends in emergency admissions were relatively unchanged between 2012/13 and 2019/20 (mean 6.7 per 1, 000, 000), and there was no significant decrease in emergency admissions during the COVID-19 pandemic. Conclusion: Day case admission rates increased between 2012/13 and 2019/20 but decreased during the COVID-19 pandemic. Emergency admission rates for patients with AAV remained relatively unchanged, despite the context of the significant disruption and reconfiguration of healthcare services. Further work on patient-level data is needed to establish whether the day case reduction is due to fewer new patients or relapsing patients being diagnosed (and therefore fewer remission induction infusions) during this period or altered clinical practice leading to postponement of planned remission maintenance treatment that would have usually been given. Alternatively, this change may reflect a change in clinical practice to preferentially use oral rather than IV agents. All of this may have future consequences both for clinical practice and individual patient care and outcomes post-pandemic. Disclosure: M. Odingo: None. M. Rutter: None. P. Lanyon: Grants/research support; Grants/research support; PCL has received funding for research from Vifor Pharma. M. Grainge: None. D. Groves: None. M. Bythell: None. J. Aston: None. S. Stevens: None. F. Pearce: Grants/research support; Grants/research support; FAP has received funding for research from Vifor Pharma.